THE IMPORTANCE OF FINANCIAL EDUCATION AND ITS RELATIONSHIP WITH ACCOUNTING PRACTICE IN DAILY LIFE (REMUNOM, 2024)
Currently, financial management has become of great importance to the financial market, due to its high degree of complexity, not only for companies but for society as a whole.People's lack of information about the financial market can cause impacts such as debt, loss of assets and economic frustration.The respective article aimed to analyze financial education and accounting practices and the incorporation where these possible areas can cooperate for people's daily financial management.The research used the descriptive bibliographic methodology with a qualitative background.Financial understandings with accounting practices showed us that society can.The research contributes to the understanding of the importance of financial education in the development of management skills and more informed financial decision-making.